Analisis Keputusan Pembelian Mobil Menggunakan Metode MOORA dalam Sistem Pendukung Keputusan - Dede Eko Saputro; Herwis Gultom (Riau Jurnal Teknik Informatika, 2025)
The purpose of this study is to analyze car purchase decisions using the Multi-Objective Optimization based on Ratio Analysis (MOORA) method. This method was chosen because it is able to handle various conflicting decision-making criteria. The study evaluated fifteen car alternatives based on seven criteria: price, fuel consumption, engine capacity, safety features, comfort, resale value, and CO2 emissions. Price and CO2 emission criteria were considered the most important, while other criteria were considered the most important. The analysis process begins with data collection and the application of criteria for value normalization for each alternative. Then, the final score is obtained by summing the normalization value of the maximized criteria and subtracting the normalization value of the minimized criteria. The results of the analysis show that the car that receives the highest score is the most suitable to buy. This research shows how the MOORA method functions in decision support systems and provides useful knowledge to consumers on how to make more informational and data-driven purchasing decisions.